2020
DOI: 10.1097/scs.0000000000005692
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Airway Identification and Management in Patients With Moebius Syndrome

Abstract: Background: Airway management in patients with Moebius syndrome can be difficult due to the presence of orofacial malformations. This paper aims to present our institution's experience in the evaluation and management of the upper airway in patients with Moebius syndrome Methodology: The authors performed a retrospective study including every patient with Moebius syndrome submitted to surgery between 2012 and 2017. Difficult airway was defined as one re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The oral abnormalities, such as a small jaw or extreme dental stenosis, can cause difficulties in mask ventilation and intubation. There are several reports on airway management of patients with Moebius syndrome [ 11 15 ], and mask ventilation has often been reported to be easy [ 13 ]. We estimated that mask ventilation was available based on his physical findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The oral abnormalities, such as a small jaw or extreme dental stenosis, can cause difficulties in mask ventilation and intubation. There are several reports on airway management of patients with Moebius syndrome [ 11 15 ], and mask ventilation has often been reported to be easy [ 13 ]. We estimated that mask ventilation was available based on his physical findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was not possible due to lack of patient cooperation, we believe it would have been safer to perform awake fiberoptic intubation or to secure the airway with spontaneous breathing remaining. Previous reports have found that overweight and obesity [ 15 ], abnormalities of mandibular/palatal structures, and four cranial nerves (IX, X, XI, XII) are statistically significant factors associated with tracheal intubation difficulties in patients with Moebius syndrome [ 13 ]. Although our patient was not overweight, several factors made tracheal intubation difficult, including mandibular/palatal abnormalities (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of the clinical problems present in patients afflicted with Moebius syndrome requires intervention by a multidisciplinary team, including pediatricians, ophthalmologists, stomatologists, rehabilitation specialists, plastic, orthopedic, and craniofacial surgeons. 10,11…”
Section: Discussionmentioning
confidence: 99%
“…This assessment is made according to the american society of anesthesiologists (ASA) is an important data, so that the anesthesiologist has the dimension of the potential risk during the anesthetic procedure (MCISAAC and colab., 2017). It is also performed the airway viability assessment, which can be done according to the Mallampati scale, which is the predictor of airway difficulty most commonly used by anesthesiology today (TELICH-TARRIBA and colab., 2019).…”
Section: Introductionmentioning
confidence: 99%